The increasing social cost of urban congestion: an educational exercise - Bazant S., Jan (Editorial Pontificia Universidad Javeriana, 2013)
Due to high population growth and the ineffectiveness of planning for our Latin American cities, they have been expanded in a piecemeal fashion. The traditional solution to organize the urban functional structure has been the improvement of its road system. Although the primary avenues and road circuits of cities are expanded and remodeled, with the increase in population and vehicles they end up congested. The text shows how these extensions in initial roadwork have a social benefit (lower travel times), but then they begin to generate a social cost, since the travel time rises due to increased downtime resulting from congestion. In conclusion, it offers a view to twenty five years of the increasing social cost urban population must pay for these failed urban policies that favor the use of cars against public transport.